Pengembangan Aplikasi Manajemen Peserta Penerima Program Keluarga Harapan Pada Dinas Sosial Kota Banjarbaru - Ihsanul Fikri (Universitas Putra Indonesia YPTK Padang, 2023)
The Banjarbaru City Social Service Office handles and processes data on the Family Hope Program (PKH) located in the Banjarbaru City area. need an aplication that manages data that determines which participants deserve assistance and the need for a system that can provide data that can reach PKH assistance. From the existing problems, it was analyzed and designed an management application for PKH recipients at the Banjarbaru City Social Service, which was built using the waterfall method, with stages including system requirements analysis and ongoing system analysis, design or design using the UML method, interface design, writing program code, testing, and implementation stages. This system produces an management application for PKH recipients at the Banjarbaru City Social Service. Forming neatly stored documentation and performance power in information systems. Documented data is stored neatly in a form database so that it is easy to find when needed.